Implementation of Structured Discharge Planning for Empowerment and Self Efficacy of Type II Diabetes Mellitus Patients - Tubagus Erwin Nurdiansyah; Aulia Rahman (Jurnal Keperawatan, 2022)
Self-efficacy is a person's belief to take action to achieve a desired goal with his abilities. The achievement of good Self Efficacy in Diabetes Mellitus patients is very dependent on the Discharge Planning provided by health workers. Discharge Planning is a process of assessing, preparing, and coordinating to facilitate the supervision of health services and services before and after returning home. Patients with type II diabetes mellitus who seek treatment in March - August 2021 at Hospital Mardi Waluyo Metro. The design in this study is a pre-experimental approach. The one group pretest-posttest design is an experimental research that uses only one group in principle and no control group using the Wilcoxon Signed Rank Test. Normality test using Shapiro-Wilk. The sampling technique in this study was purposive sampling with a sample size of 30 respondents. The results of the normality Shapiro-Wilk Test on Self Efficacy before and after being given a Discharge Planning Structured obtained p =0.740, (p <0.05), so the data is not normal. The results of the Wilcoxon Signed Rank Test obtained a p-value of 0.000 <0.05.it was concluded that there was an Implementation of Structured Discharge Planning for Empowerment and Self Efficacy on Diabetes Mellitus patients at Mardi Waluyo Metro Hospital in 2021.